Laboratory study on the influence of casting on properties of ultra-high performance fibre reinforced concrete (UHPFRC) specimens - Zofka, Adam; Paliukaitė, Miglė; Vaitkus, Audrius; Maliszewska, Dominika; Josen, Ramandeep; Bernier, Alexander (Journal of Civil Engineering and Management, 2014)
This paper presents a study on the effects of casting procedure and resulting fibre orientation on the properties of Ultra-High Performance Fibre Reinforced Concrete (UHPFRC). To investigate the impact of fibre orientation in the UHPFRC specimens, three approaches were employed. First, densities were measured from the top, middle and bottom zones of the cylinders to observe physical changes as the function of cylinder height. Secondly, two engineering fracture tests were performed in both compression and tension, and a comparison of fracture energies was conducted between different cylinder zones. While previous studies have explored the influence of steel fibres on the UHPFRC performance, the Semi-Circular Bending (SCB) and Disc Compact Tension (DCT) experimental setups have not yet been used in the UHPFRC fracture testing. Lastly, samples from different zones were scanned using X-ray computer tomography (X-ray CT). Both visual and digital image analysis of the X-ray scans were conducted in order to observe fibre orientation pattern changes within different zones. Although density calculations showed insignificant differences between different zones, fracture testing exhibited significant differences through the testing process as well as through fracture energy computations. Furthermore, X-ray CT demonstrated considerable differences in spatial fibre orientation with respect to two uniquely defined angles.